An innovative sealed shoe to off-load and heal diabetic forefoot ulcers – a feasibility study. Issue 1 (1st January 2017) - Jarl, Gustav; Tranberg, Roy
ABSTRACT: Background : Non-removable knee-high devices are the gold standard to treat diabetic foot ulcers located on the plantar forefoot, but they immobilize the ankle, which restricts daily life activities and has negative effects on joint functioning. Objective : To investigate the feasibility of sealing a therapeutic shoe to off-load and heal diabetic forefoot ulcers. Design : A case series of seven men with type 2 diabetes and a metatarsal head ulcer were prescribed therapeutic shoes and custom-made insoles. The shoe was sealed with a plastic band. Off-loading was assessed with the F-scan pressure measurement system. Adherence to wearing the shoe was assessed with a temperature sensor and by documenting the status of the seal. Results : The off-loading was effective and all ulcers healed. Median time to healing was 56 days (range 8–160). Complications were secondary ulcer ( n  = 1) and plantar hematoma ( n  = 1). Five of seven participants did not disturb the seal. Conclusions : Sealing a therapeutic shoe is a feasible way to off-load and heal forefoot ulcers. A controlled trial is needed to compare the effectiveness and safety of a sealed shoe to other non-removable devices.